Proceedings of the 16th International Conference on Informatics in Control, Automation and Robotics 2019
DOI: 10.5220/0007810101960201
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Temperature Measurement for Hot Spots in Face Region of Cattle using Infrared Thermography

Abstract: Infrared Thermography Technology (IRT) is a non-invasive method that has been used to calculate and display temperature as an Infrared thermal image. Infrared thermal images are used frequently to measure temperature remotely, and this temperature can be used as a health indicator for detecting diseases and inflammation in human and animal. In cattle, the rising temperature of the eye and nose region used for identifying stress and Bovine respiratory disease (BRD). In such applications, measuring temperature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For example, if the refresh rate of a thermal imaging device is 50 Hz, this means that the image refreshes 50 times every second (equivalent to 50 frames/s. Only a minority of studies recorded using video ( 14 , 32 , 36 , 54 , 56 , 79 , 96 , 115 ) with just one quarter of those using a frame rate >50 Hz ( 32 , 96 ) due to thermal camera capabilities. The AAT also recommend that for temperature analysis, radiometric video files are used as there is temperature data embedded in each pixel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the refresh rate of a thermal imaging device is 50 Hz, this means that the image refreshes 50 times every second (equivalent to 50 frames/s. Only a minority of studies recorded using video ( 14 , 32 , 36 , 54 , 56 , 79 , 96 , 115 ) with just one quarter of those using a frame rate >50 Hz ( 32 , 96 ) due to thermal camera capabilities. The AAT also recommend that for temperature analysis, radiometric video files are used as there is temperature data embedded in each pixel.…”
Section: Resultsmentioning
confidence: 99%
“…Image analysis techniques have traditionally utilized manual techniques to highlight regions of interest ( 52 ) and commercial IR camera software for image processing ( 100 , 110 ). More recent studies have made advances in terms of advanced statistical predictive modeling ( 31 ) and algorithm development ( 79 ). To act autonomously and yield real-time results, it is likely that techniques incorporating computer vision and neural networks will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pulsed electric fields could improve energy and yield efficiency of tomato processing by using less energy in pressing tomatoes and reducing greenhouse gas emissions [44,45]. AI-and ML-based models and technologies are being used for sustainable livestock farming, such as monitoring animal health and well-being, predicting disease, and optimizing dietary supply, intake, and consumption of nutrients [46][47][48][49][50][51]. To determine where and how to target efforts most effectively, it is necessary to capture where along the food chain, in which foods, and in which countries the greatest losses occur [52].…”
Section: Sdg 2: Zero Hungermentioning
confidence: 99%
“…The authors identified five features (clusters of data) using an ANN model, which showed strong separation between healthy and infected Ellis, Jacobs, Dijkstra, van Laar, Cant, Tulpan and Ferguson birds and were able to differentiate between healthy and infected birds with an accuracy of 66.6% on day 2 and 100% on day after infection. Similar to vocalization, infection may lead to detectable differences in movement patterns (Colles et al, 2016; optical flow analysis) and the surface temperature of animals (Jaddoa et al, 2019; IR thermal imaging), leading to earlier diagnosis of disease outbreak.…”
Section: Pattern Recognitionmentioning
confidence: 99%